Validity and Practicality of Chemical Equilibrium Electronic Student Worksheets Based on Guided Discovery Learning to Increase the Critical Thinking Ability - Sonya Frisilla; Hardeli Hardeli (Postgraduate, University of Mataram, 2022)
Chemical equilibrium is an abstract chemical material that includes concepts and calculations. The purpose of this study was to develop and produce chemical equilibrium electronic student worksheets based on guided discovery learning to improve students’ critical thinking skills and fulfill the criteria for validity and practicality. This research and development use the Plomp model which consist of three stages, namely the preliminary research phase, prototyping phase, and the assessment phase. The validity and practicality of the teaching materials developed were obtained through research instruments in the form of validation and practicality questionnaires. Validation was carried out by 6 material expert validators and three media expert validators while practicality was carried out by 40 students of 11thgrade high school students and three chemistry teachers. The data analysis technique used is Aiken’s V technique for validity and the percentage technique for practicality. The results of the analysis of the material expert validation and media expert validation data based on the average Aiken’s V value showed a result of 0.84 and 0.89 with a very valid category. The results of the practicality of the electronic student worksheets were 84.87 and 92.11 with a very high category